Formal concept analysis : 13th International Conference, ICFCA 2015, Nerja, Spain, June 23-26, 2015, Proceedings /: 13th International Conference, ICFCA 2015, Nerja, Spain, June 23-26, 2015, Proceedings. (2015) - Unknown
No abstract available